Marketing Strategy via Facebook and Instagram to Achieve Brand Awareness at Movenpick Resort & Spa Jimbaran Bali - Sekar, Ni Wayan; Sunarsa, I Wayan; Putra, Putu Gede Eka Darma (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The aim of this research is to formulate a social media strategy using the Insights feature, the REAN model and the 10 C Digital Marketing Theory at Movenpick Resort & Spa Jimbaran Bali. Experiments were carried out on content uploaded to Facebook and Instagram. The results of the analysis are strategies prepared with indicators in the REAN model which are focused on managing social media Facebook and Instagram and the 10 C Theory is used as a basis for managing content from social media. The results of the strategy formulation are activities that can be carried out to improve social media management so that it is more optimal and achieves high reach and engagement values, as well as improving content content to achieve indicators in the 10C theory and achieve brand awareness of social media users.